Coffee Business Development Strategy (Case Study at PT XYZ) - Islachudin, Muhammad Usman; Harisudin, Mohamad; Riptanti, Erlyna Wida (Universitas Panji Sakti, 2024)
The coffee business especially in the coffee shop sector to be superior to the competition is something that must be carried out in a sustainable manner by PT XYZ. Realizing this goal, PT XYZ must formulate its business development strategy. This study aims to determine internal factors (strengths and weaknesses) and external factors (opportunities and threats) which are used as the basis for formulating coffee shop business development strategies. The basic research method is descriptive with data collection techniques through in-depth interviews, focus group discussions (FGD), observation, documentation. Information was obtained through key informants who were determined purposively with the consideration of knowing the coffee shop business, namely directors, managers, supervisors, baristas, consumers, competitors, suppliers and coffee experts. Data analysis uses internal factor evaluation matrix, external factor evaluation, Grand Strategy matrix, SWOT matrix, and participatory prospective analysis. The results of the study show that the position of the grand strategy of PT XYZ is in quadrant I, which means that the strategy concentrates on market and product sustainability, product diversification, and aggressiveness. The main strategy prioritized based on the driving strategy is to increase the effectiveness and efficiency of departmental performance and improve the quality of human resources.